The Forests of Upper Assam - SenGupta, J. N. (Indian Forester, 1937)
A summary of the writer’s tour notes on plantations and other silvicultural experiments on the problem of natural and artificial regeneration in certain important centres of the evergreen forests of Upper Assam (visited during January 1937). with proposals for the future, vis-a-vis different local sub-types.